Rethinking the taxation of compensation income in the Philippines - Quimbo, Stella; Javier, Xylee (The Philippine Review of Economics, 2015)
The current individual income taxation structure of the Philippines significantly violates several norms of equity, with wage and salary workers (wsws) being disproportionately burdened by income taxes. An important source of inequity is the phenomenon of "bracket creep" resulting from the failure to adjust tax brackets by inflation. Another is the failure of a large number of the self-employed to pay the right taxes. We show that while inflation-adjustment of tax brackets results in revenue losses, an expansion of the tax base, a simplification of the income tax structure, and a reduction of tax rates can plug this leak. Using data from the merged 2013 Labor Force Survey and 2012 Family Income and Expenditures Survey, we estimate a set of tax rates that largely offsets the revenue losses from inflation-adjusted tax brackets. A key behavioral premise, supported by a multivariate logit analysis, is that the likelihood of paying income taxes increases with lower effective tax rates. Under the personal income tax structure proposed here, 36 percent of the income tax burden would be borne by the 2 top tax brackets?a seven percentage-point increase over the current share. Implementing these tax reforms, however, requires improvements in tax administration to accommodate the potential expansion in the tax base.